Effect of deep placement of nitrogen fertilizers on rice yield and N use efficiency under water regimes (SAARC Journal of Agriculture, 2016)
The experiments were conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during boro season of 2013 to evaluate the effect of deep placement of nitrogen (N) fertilizers on rice yield and N use efficiency under two different water regimes [continuous flooding (CF) and alternate wetting and drying (AWD)]. After deep placement of USG and NPK briquettes and each split application of PU, the water samples were collected for five consecutive days and analyzed for ammonium-Nitrogen (NH4-N) concentration. In both water regimes the floodwater NH4-N concentration gave highest value at the second day of PU application followed by gradual decrease with time and in continuous flooding condition the release of NH4-N was higher compared to AWD condition. Deep placement of N fertilizers also increased grain yield under AWD compared to CF condition and the maximum value was obtained in treatment T5 [USG 78 kg N ha-1 + PM 3 t ha-1] statistically similar to T3 [USG, 156 kg N ha-1]. Due to application USG and NPK briquettes, the N uptake and N use efficiency also gave higher values in AWD compared to CF condition. The results revealed that the deep placement of USG with poultry manure performed better in terms yield, N uptake and N use efficiency by BRRI dhan29 under AWD condition. So, the deep placement of USG under AWD condition could be recommended for higher production of boro rice.SAARC J. Agri., 13(2): 161-172 (2015)